2016
DOI: 10.1002/ange.201602274
|View full text |Cite
|
Sign up to set email alerts
|

An In Situ One‐Pot Synthetic Approach towards Multivariate Zirconium MOFs

Abstract: Chemically highly stable MOFs incorporating multiple functionalities are of great interest for applications under harsh environments.H erein, we presented af acile onepot synthetic strategy to incorporate multiple functionalities into stable Zr-MOFs from mixed ligands of different geometry and connectivity.V ia our strategy,tetratopic tetrakis(4-carboxyphenyl)porphyrin (TCPP) ligands were successfully integrated into UiO-66 while maintaining the crystal structure, morphology,a nd ultrahigh chemical stability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 73 publications
1
17
0
Order By: Relevance
“…According to the diffraction patterns shown in Fig. S9 (online), it can be found that pristine UiO-66 matches well with previous reports, demonstrating the crystalline structure of UiO-66 is perfectly preserved after the introduction of CuTCPP into the MOF [12]. The XRD of TiO 2 fairly conforms to the HR-TEM for plane of anatase ( Fig.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…According to the diffraction patterns shown in Fig. S9 (online), it can be found that pristine UiO-66 matches well with previous reports, demonstrating the crystalline structure of UiO-66 is perfectly preserved after the introduction of CuTCPP into the MOF [12]. The XRD of TiO 2 fairly conforms to the HR-TEM for plane of anatase ( Fig.…”
Section: Resultssupporting
confidence: 89%
“…In contrast, the color of CuTCPP & UiO-66 can be hardly washed away. Associating with previous study [12], it is thereby ascertained that the primary portion of CuTCPP displays steady coordination mofde in the CTU structure.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…These interesting compounds have been studied for possible different applications such as fuel cells [ 187 ], pervaporation [ 188 ], nanofiltration [ 189 ], gas separation [ 190 ], desammonia adsorption [ 191 ], and organocatalysis [ 192 ]. The introduction of MOFs into organic polymer results in the enhanced thermal chemical stability of the formed composites under harsh conditions, making them suitable for industrial application [ 193 ]. For elaboration of these membranes, polymers such as perfulorosulfonic acid [ 194 ], sulfonated poly (ether ether ketone) [ 195 ], and poly(vinyl alcohol) [ 196 ] have been used.…”
Section: Composite Membranesmentioning
confidence: 99%